Determinants of Polish Exports to the Ukrainian Market - Anna Lewandowska; Elżbieta Inglot-Brzęk; Ruslan Harasym (Barometr Regionalny)
The aim of this article is to diagnose the state of Polish-Ukrainian economic relations in the area of trade in goods and services, with particular emphasis on the export of goods to the Ukrainian market. The study includes an analysis of the legal conditions and statistical data on trade cooperation between Poland and Ukraine. In order to deepen the theoretical discussion, a quantitative study was carried out among Polish enterprises cooperating with Ukrainian partners, or operating on the Ukrainian market. The results are primarily focused on depicting the exports of goods and services of Polish entrepreneurs to the Ukrainian market.